Mycobacterial chylous ascites: report of three cases and systematic review - Mallick, Bipadabhanjan (Ther Adv Infect Dis, 2018)
BACKGROUND: Chylous ascites is an uncommon presentation of mycobacterial infection. METHODS: We report three cases of tubercular chylous ascites, and in addition, we performed a systematic review of the published literature for the clinical presentation, treatment, and outcomes of mycobacterial chylous ascites. We followed the PRISMA guidelines for the systematic review. RESULTS: A total of 33 cases (including three of ours) were included. The mean age of the reported cases was 32.54 ± 17.56 years, and a male predominance (76%) was noted. The predominant clinical features were abdominal distension, abdominal pain, fever and loss of appetite and weight. Mycobacterium tuberculosis (MTB) and Mycobacterium avium-intracellulare (MAC) infection were responsible for 16 and 15 cases, respectively. All patients with MAC related chylous ascites had HIV infection. The mechanisms were related to lymph nodal enlargement, constrictive pericarditis and remote scrofuloderma. Overall, there was 29% mortality. Use of anti-mycobacterial therapy with use of total parenteral nutrition, octreotide and medium chain triglyceride-based diet resulted in improvement in the rest of the cases. The cause of death in our case was anti-tubercular therapy-induced hepatitis; three deaths were due to disseminated mycobacterial infection, one due to cardiopulmonary failure and unknown in four patients. CONCLUSION: Chylous ascites due to mycobacterial infection is uncommon and associated with poor outcome. However, early diagnosis and nutritional management along with antimycobacterial therapy can improve outcome.